Detection of cavities using the method of fundamental solutions - Karageorghis, A.; Lesnic, D. (Inverse problems in science and engineering, 2009)
The determination of the boundary of a cavity, defined here as a perfectly insulated inclusion, within a conducting medium from a single voltage and current flux measurements on the accessible boundary of the medium, can be modelled as an inverse boundary value problem for harmonic functions. We propose a novel numerical solution method for this inverse problem based on the method of fundamental solutions. The algorithm for imaging the interior of the medium also makes use of radial polar parametrization of the unknown cavity shape in two dimensions (or spherical parametrization in three dimensions). This discretization yields a highly non-linear and ill-conditioned system of equations. The system is recast as a non-linear least-squares problem with penalty regularizing terms included in order to improve the stability of the numerical solution with respect to random noise introduced in the measured error-contaminated input data. The feasibility of this new method is illustrated by some numerical examples.